The feasibility of passive controlled structural mechanism method to the design of structures. (15th January 2018) - Chadad, Liran; Vilnay, Oren; Levy, Robert; Ornai, David
Highlights: Controlled mechanisms has better blast resistance capacity. The controlled member remains within elastic regime during the entire response. The regular frame is losing its stability for the same impact. Abstract: Passive control of structures to sustain blast loads is extremely important; however, the current research literature and existing technologies are rather limited. The major challenge lies in the fact that the control system should operate rapidly during a very short period of time. In this work it is proposed to overcome this difficulty by changing the structure into a mechanism and by using shear and moment passive control devices attached to the structural members in a sophisticated manner to form "Passive controlled structural mechanism (PCSM)". The friction devices are located at the joints of the structural members, they are designed so that under mundane loading they are locked and fully transfer the forces and moments acting between the members, while in the case of blast loadings, they transfer predetermined force Fr and moment Mr between the members. Thus, the blast response of the structure is defined by the forces and moments induced by the friction devices. These forces and moments are designed so that they do not exceed the elastic capacity of the structural members, and no damage or collapse will occur. The blast energy is absorbed mainly by the rigid body movement of the structural members and not by the structural members' flexure. The blast response of a PCSM reinforced concrete (RC) column and frame are investigated by using an analytical model and a finite elements method (FEM) model. It is shown that the PCSM structure remains intact in the elastic regime while regular structures are losing their stability for the same impact.